Analisis Nilai Karakter Peduli Sosial Pada Perkumpulan Kelompok Siswa Sdn 01 Bono Tulungagung - Cahyono, Budi Enggar; Setyo Jadmiko, Rahmad (Jurnal Pendidikan Tambusai, 2023)
The study group association is the processing of students in learning activities, namely active, innovative, creative, and fun learning. This research examines class V which conducts student study groups. In conducting this analysis, descriptive qualitative research is used, namely by conducting data collection techniques regarding matters to be obtained through observation, questionnaires, interviews and documentation. The results of the research that have been obtained through observations, interviews, and distributing questionnaires are that it can be known that fifth grade students at SDN 1 Bono, Boyolangu Subdistrict, Tulungagung Regency mostly already have a sense of social concern, even though there are a small number that still need to be improved in terms of social care according to data that has been obtained through observations and strengthened through interviews with class teachers.